Compliance Risk Management Tax Supervision of Village Government Agencies: Case Study of KPP Pratama Jember - Akbar, Moh Abrori; Wibowo, Buddi (SUBSTANSI, 2024)
Research objective: This research aims to create a compliance risk map for village government agencies (IPDes) in KPP Pratama Jember, to inform monitoring and education priorities Method: In-depth interviews were conducted and analyzed qualitatively using thematic analysis to gain a deeper understanding of the phenomenon under study and machine learning techniques were utilized for data mapping Research findings: The resulting risk map categorized 14 IPDes as high-risk, prioritizing them for targeted supervision and intervention efforts. Practical implication: This research is expected to provide additional insights into the application of CRM to IPDes. The development of IPDes CRM needs to be considered by the Directorate General of Taxes (DGT) to be realized considering that no tool can be used to prioritize IPDes supervision. Furthermore, this study can be a trigger for the development of CRM at the national level, and village tax compliance can be a variable in the distribution of regional transfers Keywords: Compliance Risk Management, village government agencies (IPDes), village income and expenditure allocations (APBDes).